LYMPHEDEMA TREATMENT CERTIFIED PHYSICAL THERAPISTS' AWARENESS OF AND PRACTICE PATTERNS FOR SIDE EFFECT RISK REDUCTION AFTER BREAST CANCER TREATMENTS (International Journal of Physiotherapy, 2019)
Background: Lymphedema and other side effects (SEs) of breast cancer (BC) treatments are a clinical condition; hence, input based on clinical experience is highly relevant for deciding on intervention.Purpose: To evaluate lymphedema treatment certified physical therapists' (CLT) awareness of SEs after BC treatments and their recommendations for risk-reduction.Methods: In a mixed model qualitative study, a convenience sample of 20 CLTs with at least 5-years' experience were interviewed by phone call. Topics discussed were SEs after BC treatments and recommendations for risk reduction.The authors analyzed the data separately and then discussed the interpretation of similarities and differences.Results: The most frequently mentioned SEs were arm lymphedema, breast swelling, pain, and shoulder movement limitation. General SEs, such as stress and anxiety, were also mentioned. There was consensus on the need for education about lymphedema, infection prevention, and physical activity, but not on the optimal timing to provide instruction, orfor a preliminarysession with a CLT.Conclusions: The participants wereaware of and knowledgeable about common SEs after BC surgery and preventive interventions, in keeping with "best practice" recommendations. However, remaining controversies raise the need for a practical guideline for SEs risk reduction after BC surgery.